2019
DOI: 10.1177/0284185119826549
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial fat, left ventricular strain, and T1-relaxation times in obese individuals with a normal ejection fraction

Abstract: Background Cardiac magnetic resonance (CMR) may detect early signs of cardiomyopathy. Purpose The purpose of this CMR study was to evaluate epicardial fat volume (EFV), T1-relaxation times (T1), and left ventricular (LV) strain in non-obese (<30 kg/m2) and obese (>30 kg/m2) individuals with no other cardiovascular risk factor and with a normal LV ejection fraction (LVEF) to detect early changes of obesity cardiomyopathy. Material and Methods Seventy-five individuals (38 men) without additional cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
4
8
0
Order By: Relevance
“…The present study did not find any significant differences in LVEF between adults with uncomplicated obesity and HCs, which is consistent with results of previous reports (4,5,23). However, impaired LV contractility was detected during strain analysis, with global radial, circumferential, and longitudinal PS being lower in the obesity group than the HC group.…”
Section: Obesity and Cardiac Dysfunctionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study did not find any significant differences in LVEF between adults with uncomplicated obesity and HCs, which is consistent with results of previous reports (4,5,23). However, impaired LV contractility was detected during strain analysis, with global radial, circumferential, and longitudinal PS being lower in the obesity group than the HC group.…”
Section: Obesity and Cardiac Dysfunctionsupporting
confidence: 92%
“…These results indicate that PS has higher sensitivity than LVEF as marker for subclinical myocardial contractile dysfunction. Similar results were reported by Homsi et al (23), who reported that their obesity group had lower mean LV longitudinal and circumferential strain on CMR than their non-obesity group. However, previous echocardiographic studies revealed decreased longitudinal strain, increased or decreased radial strain, and reduced or no marked changes in circumferential strain among children with obesity (24,25).…”
Section: Obesity and Cardiac Dysfunctionsupporting
confidence: 90%
See 1 more Smart Citation
“…Multiple studies in older adults have reported reduced systolic strain with preserved ejection fraction in obesity, hypertension, and T2DM ( 10 , 14 , 15 , 24 , 26 ). For example, cardiac MRI studies measuring global circumferential end-systolic strain have reported a clear reduction in obesity ( 14 ), and progressive decline from controls to hypertension to hypertension with T2DM ( 15 ). Evidence of reduced systolic strain in younger asymptomatic populations is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…In mature patients with T2D, ECV was mainly higher without clear changes in native T 1 values (21). In both younger and older adult obese populations, no differences were reported in native T 1 values and ECV (22,23). T 2 mapping values have only been reported in mature hypertensive and T2D subjects, both show higher values than in healthy controls (24,25).…”
Section: Introductionmentioning
confidence: 97%